A Publicidade ilícita nas redes sociais: hipermodernidade e consumo em ambiente digital - ESTEVES, André Luiz Silveira (2022)
The overcome of the Modernity paradigm and the consequent imertion of the citizens in the so called Hypermodernity has brought reflects in diferent parts of life in Society, in a way that the transformation of consume Society has broght new perspectives for the act of consume. In this sense, it’s necessary to bring to debate how the Hypermodernity consequences affects the consumer, and also the influence of technological resources used by the industry to map consume preferences and to dissiminate tendencies in the digital enviroment. Likewise, with emerge of the digital influencers and the social midias, it’s up to the Law to procede the analisys of theese agents reflects in consume relations, in the view of the consumers vulnerability escalation owing to the presente social conjecture. Therefore, it’s fundamental to bring the discussion about the national’s court’s compreenhention over the legal responsability of the digital influencers and digital plataforms, with the pourpose of analise if the majority decisions it’s still enough to apreheend the actual situation and to promote the better conflicts solution about the Consumers Rights, for this, the deductive method was used, and the bibliographic survey was used as a technique.